Factors Affecting Pediatric Dyslipidemia Screening and Treatment. (May 2019) - Herrington, Lisa; Susi, Apryl; Gorman, Gregory; Nylund, Cade M.; Hisle-Gorman, Elizabeth
Identification and management of dyslipidemia in childhood can reduce future cardiovascular risk. We performed a retrospective cohort study of children ages 2 to 18 years during 2009 to 2013 to evaluate factors that affect screening and treatment of pediatric dyslipidemia related to 2011 National Heart, Lung, and Blood Institute (NHLBI) guidelines. Logistic regression analysis determined the impact of NHLBI-identified factors on odds of being screened, elevated low-density lipoprotein cholesterol (LDL-C), and receiving pharmacotherapy. A total of 1 736 032 children were included; 113 780 (6.6%) were screened for dyslipidemia. Screening in 9 to 11 year olds increased from 2009 to 2012. Of children screened, 18 801 (16.5%) had elevated LDL-C; 425 (2.3%) were treated pharmacologically. Parental dyslipidemia, diabetes mellitus, chronic kidney disease, Kawasaki disease, human immunodeficiency virus infection, nephrotic syndrome, liver, thyroid, and other endocrine disorders increased odds of screening. Older age, nephrotic syndrome, chronic kidney disease, diabetes mellitus, and hypertension increased odds of having elevated LDL-C and receiving treatment. Pediatric dyslipidemia screening rates remain low.